New methods in diagnosis and therapySuccessful percutaneous coronary intervention using a 4-in-3 “Slender Mother and Child” PCI technique - Honda, Tsuyoshi; Fujimoto, Kazuteru; Miyao, Yuji (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We report two cases of successful percutaneous coronary intervention (PCI) using a 4-in-3 “Slender Mother and Child” PCI technique. In both cases, coronary angiography revealed severe stenosis of the right coronary artery (RCA). In both cases, 5-Fr sheathless guiding catheters were inserted into the RCA (virtual 3-Fr PCI) but stents could not pass through because of stents previously implanted at the proximal site of the target lesions. After 4-Fr straight “child” guiding catheters were inserted into the 5-Fr sheathless “slender mother” guiding catheters, they were deployed successfully at the target lesions. This system might be useful to improve stent delivery in virtual 3-Fr PCI.